Assessing Numerical Analysis Performance with the Practi Mobile App - Maria Cutumisu; Kristin Garn; Raymond J. Spiteri (MDPI AG, 2024)
Numerical analysis is a unique combination of mathematical and computing skills. It facilitates a deeper understanding of data analytics and machine learning software libraries, which are exploding in use and importance. However, it is a topic that continues to challenge students because it requires a confluence of conceptual, procedural, and computational skills and associated pedagogies. Therefore, it is valuable to identify effective pedagogies and tools to enhance and assess student numerical analysis skills. Despite the proliferation of mobile technology in postsecondary education, its role in the context of numerical analysis is largely unknown. This quasi-experimental pilot study used Practi, an educational mobile app designed to assess numerical analysis performance and promote both retrieval practice and deliberate practice, which have been shown to help improve performance and develop expertise. Participants were 32 undergraduate students enrolled in a second-year introductory Numerical Analysis course at a large North American university. They were prompted to use Practi to solve quizzes on a regular basis throughout the course, before and after each lecture, to promote deliberate practice and spaced retrieval. Results of a paired t-test analysis showed that Practi was able to detect improvement in student quiz performance after the lectures compared to before the lectures. Additionally, performance on the Practi quizzes after the lectures was positively associated with the overall course performance. This suggests that mobile apps supporting deliberate and retrieval practice can complement more traditional means of instruction and assessment of numerical analysis in postsecondary mathematics education.